SUPPLY OF CASSAVA IN MAGELANG DISTRICT CENTRAL JAVA PROVINCE - Candarisma Dhanes Noor Viana; Ali Hasyim Al Rosyid; Wahyu Adhi Saputro; Sri Hidayati; Eka Nur Jannah (Universitas Tidar, 2023)
Cassava is a commodity that has the potential to be developed into a regional superior product. Cassava can be processed into other forms of food that are consumed by the community and one of the centers is in Magelang Regency. This study aims to analyze what factors influence the supply of cassava in Magelang Regency. The data used comes from secondary data. The data used from 2008 to 2022 comes from the Central Bureau of Statistics. The results of the study stated that the supply of cassava in Magelang Regency was jointly influenced by the previous year's cassava price, the previous year's sweet potato price, the previous year's cassava production, the harvested area of ​​the previous year's cassava, the previous year's corn price. Meanwhile, partially the supply of cassava in Magelang Regency was influenced by the price of sweet potatoes in the previous year and the cassava harvested area in the previous year. Based on the results of the analysis, the price elasticity of cassava in the previous year on cassava supply in Magelang Regency was inelastic for both short-term elasticity (0.701) and long-term elasticity (0.02).